Hygroscopic materials and characterization techniques for fiber sensing applications: a review - Riza, Muhammad Arif; Go, Yun Ii; Maier, Robert R. J.; Harun, Sulaiman Wadi; Anas, Siti Barirah (M Y U Scientific Publishing Division, 2020)
Various characterization techniques are used in the study of materials in order to understand their properties. Data and observation recording characterization of a material is done by researchers for various properties within various environments. One of the many properties that make a material attractive for use in certain devices is hygroscopicity. Various techniques for characterizing hygroscopicity have been developed and utilized. However, since these techniques are not usually the highlights of studies, there has been limited acknowledgement of the usefulness of hygroscopicity testing. This review introduces several established characterization techniques allowing researchers to fully characterize materials in terms of their hygroscopicity. The full potential of hygroscopic materials can be seen in their use in various fiber sensors. The deformation of materials upon exposure to water molecules can be utilized to perturb sensing elements in fiber sensors, allowing the user to take full advantage of the hygroscopicity of the material.